FENOMENA SEBELUM BANJIR SEBAGAI REFLEKSI INDIVIDUALISTIS WARGA KELURAHAN SURAU GADANG KECAMATAN NANGGALO KOTA PADANG - -, Marni - (Pendidikan Sosiologi, 2014)
This thesis examines the phenomenon before the flooding as a reflection of individualistic Villagers Surau Gadang subdistrict Nanggalo Padang City. City Padang is highly vulnerable flood moreover, is attested from Padang BMKG data showing high levels of rainfall in the Padang City. In 2013 almost all the districts in the Padang City flooded one Sub. In one of the villages Sub including flood prone Villages Surau Gadang. This is proved from the information society that says if it rains 2-3 hours this area flood inundation at certain points with different heights. In accordance with the above problems, the principal investigators of the problem formulated as follows : How individualistic reflection Village Surau Gadang Residents Nanggalo Padang City?The theory used in this research is the theory of organic solidarity and mechanical solidarity by Durkheim. Communities in Solidarity mechanics have a strong bond because all are generalists and have similar activities while organic solidarity together with differences in the facts and all of them have their respective responsibilities. The study uses descriptive type of data that is collected in the form of words, pictures, and not numbers. Informants in this study consisted of 12 people and the people who observed or interviewed is the main source. Data collection tools and techniques used were observation and interviews. Data collection tools such as interview guides, books, pens and tape recorders.The results of this study describes the city of Padang is one of the cities included flood-prone, based on data from BMKG Padang that includes cities that have high levels of rainfall. Surau Gadang the Village is one of the flood prone areas. In the village there is mutual cooperation activities undertaken several years but this is no longer because of busy village community so it does not happen. Almost in general got in the village Surau Gadang buried rocks, grass and piled with cement so that the drains be not smooth, and the public does not care about it. The public also does not care about the superficiality got going on in this district and let only superficial therefore flooding still occurs. Community leaders and the village did not impose sanctions on people who do not keep their environment, so that people do not care about the environment and keep it in order to avoid flooding.